In their own words: recovery after emergency general surgery in the older patient - Vanessa P Ho; Mary Joan Roach; Kristen A Berg; Divya L Deverakonda; Peter Kanuika; Brianna Arko; Adam T Perzynski (Trauma Surgery & Acute Care Open, 2023)
Objectives Emergency general surgery (EGS) conditions, such as perforated intestines or complicated hernias, can lead to significant postoperative morbidity and mortality. We sought to understand the recovery experience of older patients at least 1 year after EGS to identify key factors for a successful long-term recovery.Methods We conducted semi-structured interviews to explore recovery experiences of patients and their caregivers after admission for an EGS procedure. We screened patients who were aged 65 years or older at the time of an EGS operation, admitted at least 7 days, and still alive and able to consent at least 1 year postoperatively. We interviewed the patients, their primary caregiver, or both. Interview guides were developed to explore medical decision making, patient goals and expectations surrounding recovery after EGS, and to identify barriers and facilitators of recovery. Interviews were recorded and transcribed, and we used an inductive thematic approach to analysis.Results We performed 15 interviews (11 patients and 4 caregivers). Patients wanted to return to their prior quality of life, or ‘get back to normal.’ Family was key in providing both instrumental support (eg, for daily tasks such as cooking, driving, wound care) and emotional support. Provision of temporary support was key to the recovery of many patients. Although most patients returned to their prior lifestyle, some also experienced depression, persistent abdominal effects, pain, or decreased stamina. When asked about medical decision making, patients expressed viewing the decision for having an operation not as a choice but, rather, the only rational option to treat a severe symptom or life-threating illness.Conclusions There is an opportunity in healthcare to provide better education for older patients and their caregivers around instrumental and emotional support to bolster successful recovery after emergency surgery.Level of evidence Qualitative study, level II.